Brand upon the brain! - Negin, Louis 1929-; Staczek, Jason 1965- (The Criterion Coll., 2008)
This eerie excursion into the Gothic recesses of Maddin's mad, imaginary childhood is a nightmare set in a lighthouse on grim Notch Island, where fictional protagonist Maddin was raised by an ironfisted, puritanical mother.
Aspect ratio, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: USA, Kanada 2006
Enth. narration tracks by Isabella Rossellini, Laurie Anderson, John Ashbery, Guy Maddin, Louis Negin, and Eli Wallach ; "97 Percent True", a new documentary featuring interviews with the director and his collaborators ; deleted scene ; a new essay by film critic Dennis Lim
Keywords: Islands -- Drama; Lighthouses -- Drama; Mothers and sons -- Drama; Feature films; Science fiction films; Short films; Video recordings for the hearing impaired; Science fiction - Feature